PENGARUH TINGKAT EKONOMI, PENGETAHUAN PAJAK DAN KEPERCAYAAN MASYARAKAT TERHADAP KEPATUHAN PAJAK BUMI DAN BANGUNAN DENGAN KONTROL PETUGAS DESA SEBAGAI VARIABEL MODERATING - Wahyu Purwanto, Fadjar Harimurti & Dewi Saptantinah Puji Astuti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
This research aims to know the factors that influence tax payer compliance Land and buildings in District of Sumberlawang, by a factor of economic level, tax knowledge and public trust with the control officer rural/urban villages as a moderating variable. The object of this research in district of sumberlawang. The respondents in this study a number of 100 tax payers with sampling technique using Accidental Random Sampling. This research is quantitative research using primary data collection techniques, data in the form of survey methods, direct observations and questionnaires. Method of analysis used in this study was multiple linear regression test and absolute difference test. The results of this study show that, Level Economic, Tax Knowledge and Public Trust either partially or Simultaneous positive and significant effect against a Tax Compliance Payers Land and Buildings in District of Sumberlawang. As for the moderating variable Control Officer Rural Village only can strengthen influence of the variable economic level and tax knowledge as for the variable thus weakens publict trust. Keywords: Economic Level, Tax Knowledge, Public Trust, Control Officer Rural Village, Tax Compliance.